Bariatric surgery and the incidence of rheumatoid arthritis – a Swedish Obese Subjects study. (18th July 2019) - Maglio, Cristina; Zhang, Yuan; Peltonen, Markku; Andersson-Assarsson, Johanna; Svensson, Per-Arne; Herder, Christian; Rudin, Anna; Carlsson, Lena
Abstract: Objective: The aim of this study was to determine the effect of bariatric surgery on the incidence of RA in participants of the Swedish Obese Subjects (SOS) study. Methods: The SOS is a longitudinal study aiming to assess the effect of bariatric surgery on mortality and obesity-related diseases. This report includes 2002 subjects with obesity who underwent bariatric surgery and 2034 matched controls; none of them had RA at baseline. Cases of incident RA were identified through the Swedish National Patient Register by searching for International Classification of Diseases codes. Both intention-to-treat analyses and per-protocol analyses are reported. In the per-protocol analysis, participants from the control group who underwent bariatric surgery later on during follow-up were censored at the time of surgery. Results: During follow-up, 92 study participants developed RA. The median follow-up was 21 years (range 0–29). Bariatric surgery was neither associated with the incidence of RA in the intention-to-treat analysis [hazard ratio (HR) 0.92 (95% CI 0.59, 1.46), P = 0.74], nor in the per-protocol analysis [HR 0.86 (95% CI 0.54, 1.38), P = 0.53]. Weight change at the 2 year follow-up, expressed as the change in BMI compared with baseline, did not associate with the development of RA. Higher serum CRP levels and smoking associated with the future development of RA independent of other factors. Conclusions: We did not detect any association between bariatric surgery and the incidence of RA in subjects affected by obesity followed up for up to 29 years. ClinicalTrials.gov: (http://clinicaltrials.gov ): NCT01479452.